A Treaty over Troubled Waters: The relationship between water treaties and conflict in shared water-basins - Lascelle, James (Université d'Ottawa | University of Ottawa, 2015)
Many sources of recent literature suggest a growing concern regarding conflict over freshwater. Since freshwater is both the source of economic growth and human livelihood, one can expect that sharing its management are bound to generate conflict. To avoid disagreements from escalating, many states have established treaties regulating the use and consumption of shared rivers. However, the influence of water treaties on reducing regional tensions over water use requires further research. Thus, this paper attempts to determine whether water-sharing treaties can be used a mechanism to reduce conflict. This begs the question: do transboundary water treaties have an influence on reducing conflict between shared water-basin countries? In order to determine this relationship, this paper has drawn from three case studies, the Indus, Mekong, and the Nile river basin for a comparative case study design. I have compared the level of conflict before and after the treaties were introduced in the Indus and Mekong, to determine whether the treaties had an influence on conflict or cooperation. Subsequently, I compared the results in the Indus and Mekong to the Nile basin, which does not have a treaty. Results have shown that while water treaties do not necessarily have an influence on reducing transboundary conflict, they may have an influence on preventing conflict from escalating. This study further found that water scarcity, high water withdrawals, and particular treaty provisions were more likely to influence conflict in shared river basins. Thus, it is argued that while water sharing treaties do not necessarily have an influence on limiting the instances of conflict, they do likely a strong relationship with reducing the degree of conflict since they provide a system to resolve issues before they escalate.